2003
DOI: 10.1029/2003gl018670
|View full text |Cite
|
Sign up to set email alerts
|

Opal‐A/opal‐CT phase boundary inferred from bottom‐simulating reflectors in the southern South Korea Plateau, East Sea (Sea of Japan)

Abstract: Multi‐channel seismic reflection profiles from the trough areas of the southern South Korea Plateau, East Sea (Sea of Japan), reveal high‐amplitude, positive‐polarity bottom‐simulating reflectors (BSRs) at about 500 ms two‐way travel time (ca. 450 m) below the seafloor. The positive polarity and no noticeable drop of frequency (low‐frequency shadow) below the BSR strongly suggest that the BSR is due to an opal‐A/opal‐CT phase boundary. The BSR often marks a sharp interface between low‐amplitude reflections abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 12 publications
(18 reference statements)
0
11
0
Order By: Relevance
“…The positive acoustic impedance contrast between the transition from opal A above to opal CT below yields the same BSR polarity as the seafloor reflection. The above diagenetic transformation is likely to occur in siliceous sediments of biogenic origin (e.g., oozes, Kastner et al, 1977) and therefore this type of BSR is reported to exist in passive continental margins with slow rate of sedimentation (e.g., Berndt et al, 2004;Lee et al, 2003). The study area off SW Taiwan is characterized by rapid sedimentation with large amounts of orogenic detritus (Yen and Lundberg, 2006) derived from the rapidly denudating Taiwan island (Dadson et al, 2003) and systematic analyses of seafloor sediments found no siliceous ooze (Jiang et al, 2006) in both regions of the accretionary wedge and adjacent South China Sea continental slope.…”
Section: The Nature Of Bsr In the Study Areamentioning
confidence: 97%
“…The positive acoustic impedance contrast between the transition from opal A above to opal CT below yields the same BSR polarity as the seafloor reflection. The above diagenetic transformation is likely to occur in siliceous sediments of biogenic origin (e.g., oozes, Kastner et al, 1977) and therefore this type of BSR is reported to exist in passive continental margins with slow rate of sedimentation (e.g., Berndt et al, 2004;Lee et al, 2003). The study area off SW Taiwan is characterized by rapid sedimentation with large amounts of orogenic detritus (Yen and Lundberg, 2006) derived from the rapidly denudating Taiwan island (Dadson et al, 2003) and systematic analyses of seafloor sediments found no siliceous ooze (Jiang et al, 2006) in both regions of the accretionary wedge and adjacent South China Sea continental slope.…”
Section: The Nature Of Bsr In the Study Areamentioning
confidence: 97%
“…Hein et al, 1978;Nobes et al, 1992a;Davies and Cartwright, 2002;Lee et al, 2003). Hein et al (1978) suggested the opal-A to opal-CT boundary, which is parallel to the present-day seabed in the Bering Sea, is a time transgressive boundary and not hosted by a lithology of a single age.…”
Section: Implications For Hydrocarbon Explorationmentioning
confidence: 98%
“…Because temperature is one of the dominant controls on the silica reactions the opal-A to opal-CT diagenetic boundary may be isothermal marking a specific temperature at which the reaction occurred over extensive areas of basins (Hein et al, 1978;Kuramoto et al, 1992;Lee et al, 2003). Therefore, opal-A to opal-CT boundaries have tentatively been used as low-temperature present-day isothermal markers to help reconstruct the thermal history of the basin in order to determine source rock maturity and the timing of the maturation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A fourth type of BSR, known as diagenetic BSRs, form as the result of diagenetic boundaries in siliceous 78 sediments where sediment density increases with depth, most commonly due to the transformation of 79 biogenic silica (opal-A) to opal-CT (Berndt et al, 2004;Davies and Cartwright, 2002;Goldberg et al, 80 1987). The acoustic impedance associated with the relative change in density results in a prominent 81 reflection with the same polarity as the seafloor; this reflection follows an isothermal gradient, and 82 therefore parallels seafloor topography (Davies and Cartwright, 2002;Lee et al, 2003). This is unlike 83…”
Section: Introduction: 31mentioning
confidence: 99%